Inheritance of anthracnose resistance in the andean common bean cultivar BRSMG Realce. - GOMES-MESSIAS, L. M. (2021)
Anthracnose, caused by the fungus Colletotrichum lindemuthianum (Sacc. and Magn.), is one of the most important diseases affecting the common bean (Phaseolus vulgaris L.) in Brazil. Based on the level of susceptibility shown by the cultivars, the occurrence of environmental conditions favorable to the development of the disease, and the amount of initial inoculum present, losses in the seed yield and quality can range from 80 to 100%. The main goal of the present work was to identify the inheritance of anthracnose resistance in the Andean cultivar BRSMG Realce.